Polythionine-decorated magnetic nanoparticles as a robust and highly effective sorbent for mercury determination in environmental water samples. Issue 11 (1st September 2016) - Mehdinia, Ali; Mashkani, Masoumeh; Jabbari, Ali
ABSTRACT: Extraction, pre-concentration and determination of trace amounts of mercury ions from water samples were investigated by magnetic solid phase extraction (MSPE) method using Fe3 O4 nanoparticles decorated with polythionine as an adsorbent. A simple chemical synthesis by catalytic reaction of thionine in the presence of FeCl3 and hydrogen peroxide was used for preparation of the magnetic sorbent. Scanning electron microscopy, transmission electron microscopy, energy-dispersive X-ray spectroscopy, vibrating sample magnetometer analysis and Fourier transform infrared spectroscopy were used to characterise the adsorbent. Mercury ions were determined by cold vapour atomic absorption spectrometry. The parameters for MSPE procedure, such as pH of the extraction solution, adsorption time, weight adsorbent, elution conditions (type, concentration and volume of the eluent), volume of the sample solution and effects of coexisting ions were investigated. The obtained optimal conditions were: sample pH of 4; sorbent amount of 4 mg; sorption time of 20 min; elution solvent of HNO3 (0.3 mol L −1 )/thiourea (2% w/v) with volume of 2 mL, and breakthrough volume of 400 mL. A good linearity in the concentration range of 0.025–40 µg L −1 ( R 2  > 0.999) with the pre-concentration factor of 198 was obtained. The limits of detection and quantification were achieved as 0.008 and 0.025 µg L −1, respectively. Furthermore, sea and river water samples were analysed and good recoveries (97.1–99.6%) were obtained.